Impact of electrically activated water fractions on solubility of meat proteins - Віннікова, Людмила Григорівна; Пронькіна, Ксенія Володимирівна (Technology audit and production reserves, 2015)
The article examines and discusses the influence of electrically activated water on the proteins of muscle tissue. The aim of the study is to improve the solubility of proteins in muscle tissue to achieve greater yields and improve their quality through the use of electrically activated water fractions. The results of the studies of solubility change of sarcoplasmic and myofibrillar proteins are given. It is established the solubility level of sarcoplasmic and myofibrillar proteins in the presence of a catholyte, anolyte and drinking tap water (control). The efficiency of using electrically activated water fractions to improve the solubility of proteins in muscle tissue is shown. It is determined the dependence of the water-holding and fat-holding capacity, emulsifying capacity and emulsion stability on the protein solubility under the influence of the electrically activated water fractions. The results can be used in the production technology of emulsified sausage.